Kompetensi Guru Zaman Now dalam Menghadapi Tantangan di Era Revolusi Industri 4.0 - Shalahudin Ismail; Suhana Suhana; Eri Hadiana (Jurnal al-Thullab, 2020)
The purpose of this study is to examine how the competence of teachers today in facing challenges in the era of the industrial revolution 4.0. The method used in this study is a concept study, in which the author bases on data sources or references in the form of texts from the opinions of experts that have been formulated in the form of books, journals, and others. The results of the concept study conducted by researchers through several references state that the competence of teachers today in facing challenges in the era of the industrial revolution 4.0 is educational competence, competence for technological commercialization, competence in globalization, competence in future strategies, and competence counselor. AbstrakTujuan penelitian ini adalah untuk mengkaji bagaimana kompetensi guru zaman now dalam menghadapi tantangan di era revolusi industri 4.0. Adapun metode yang digunakan dalam penelitian ini adalah kajian konsep, dimana penulis mendasarkan pada sumber-sumber data atau referensi yang berbentuk teks dari pendapat para ahli yang telah diformulasikan dalam bentuk buku, jurnal, maupun yang lainnya. Hasil kajian konsep yang dilakukan oleh peneliti melalui beberapa referensi menyebutkan bahwa kompetensi guru zaman now dalam menghadapi tantangan di era revolusi industri 4.0 adalah educational competence,  competence for technological commercialization,  competence in globalization,  competence in future strategies,   conselor competence.